British penetration into the Libyan economy (1952-1969) - Al-Dulaimi, Waleed Abood Mohammed; Ali, Zeina Muslim Darwish (Al-Adab Journal, 2022)
The interest and rivalry of Western countries in Libya has been the subject of widespread controversy among researchers, as it appeared in several studies that addressed the political and social aspects, while neglecting Britain's role in the Libyan economy after it replaced Italy. Accordingly, this research came under the title: British penetration into the Libyan economy (1952-1969), to shed light on the nature of Britain’s policy towards the Libyan economy and its blatant interference in all its activities, especially its entry into the sterling region, and limiting the absolute authority of Barclays Bank to make investment decisions within Libya until The National Bank was established in 1955, and the Libyan Development and Stability Agency adopted a set of projects in Libya, the importance of agricultural crops in it, especially the alliance, and the impact of trade and the quality of exports and imports between Britain and Libya. The research is trying to unmask the ways of Britain’s economic exploitation of Libya in various banking, agricultural and commercial aspects? What are its objectives of the subsidies and financial aid it granted to Libya?